Adenovirus infection among pediatric patients with cancer and in pediatric recipients of hematopoietic stem cell: A multicenter nationwide study. Issue 12 (11th July 2020) - Zając‐Spychała, O.; Pieczonka, A.; Wachowiak, J.; Frączkiewicz, J.; Salamonowicz, M.; Kałwak, K.; Gorczyńska, E.; Kazanowska, B.; Wróbel, G.; Chybicka, A.; Czyżewski, K.; Dziedzic, M.; et al.
Abstract: The aim was to evaluate the incidence, clinical course, and outcome of adenoviral infection (AdVI) in pediatric patients diagnosed and treated due to cancer and in pediatric recipients of hematopoietic stem cell. Over a 72‐month period, all‐in 5599 children with cancer: 2441 patients with hematological malignancy (HM) and 3158 with solid tumors (ST), and 971 patients after transplantation: 741 after allogeneic (allo‐HSCT) and 230 after autologous (auto‐HSCT) were enrolled into the study. Among cancer patients, 67 episodes of AdVI appeared in 63 (1.1%) children, including 45 (1.8%) with HM and 18 (0.6%; P  < .001) with ST. Within transplanted patients, AdVIs were responsible for 88 episodes in 81 (8.3%) children ( P  < .001), including 78 (10.5%) patients after allo‐HSCT and 3 (1.3%) after auto‐HSCT. Time to develop AdVI was short, especially after allo‐HSCT. The most common clinical manifestation in cancer patients was enteritis diagnosed in 63 (94.0%) cases, while among HSCT recipient asymptomatic adenoviremia was found in 36 (40.9%) cases and the most common clinical manifestation was urinary tract infection. Cancer patients with disseminated disease, as well as HSCT recipients with either asymptomatic viremia or disseminated disease, received antiviral treatment. The most commonly used first‐line therapy was cidofovir. None of the cancer patients died due to AdVI, while within HSCT recipients three patients developed disseminated adenoviral disease and died despite antiviral treatment. In cancer patients, AdVIs are rare and associated with very good prognosis even without specific treatment. However, in allo‐HSCT recipients, disseminated disease with fatal outcome is more likely to occur. Highlights: Low incidence of HAdV causing less severe infections not requiring antiviral therapy but with satisfactory outcome within cancer patients. In allo‐HSCT recipients disseminated disease requiring antiviral drugs and at risk of fatal outcome is more likely to occur. Monitoring for HAdV in all patients, and especially in those who underwent AdVI prior to HSCT or had MD or MMUD‐HSCT, at early posttransplantation period should be recommended.